Junior High School Principal's Strategy in Preparing the Generation to Face the Era of Society 5.0 - Then, Yoana Merilla Kurniawan; HS, Sufyati; Ramdhani, Sendi (research, training and philanthropy institution Natural Aceh, 2024)
This research was conducted at Parahyangan Mulia Junior High School. The research subject is the principal of Parahyangan Mulia Junior High School Tasikmalaya because the principal is a leader and policy maker at school and must have a specific strategy regarding every policy he takes to deliver those goals. The goal of this research is to analyze the strategy used by the principal in preparing the generation to enter the era of society 5.0. A qualitative approach was employed in this research, and interviews, observations, and literature reviews were used as data collection techniques. The informants were the principal, head of the school team, teachers, and Parahyangan Mulia Junior High School students. The result of this research is the strategy of the principal in preparing the generation for the era of Society 5.0 is carried out through the development of the school's human resource program (character program, STEAM, and life skills) and cooperation with the stakeholders who have the same goals with the school. By implementing this strategy, the abilities of Parahyangan Mulia Junior High School students have increasingly developed according to the personality expected in the era of society 5.0, namely creative, critical, communicative, and collaborative.